Pengaruh Durasi Tidur terhadap Fokus Belajar dan Daya Ingat Mahasiswa Pendidikan Teknik Otomotif Universitas Pendidikan Indonesia - Muhammad Ajib Nurzaki; Ridzki Ramadhan; Wahid Munawar (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Sleep is a fundamental physiological need that directly influences cognitive performance, including the ability to focus and retain information. College students are among the most sleep-deprived populations due to academic pressure, heavy workloads, and digital lifestyles that encourage late-night activities. This study aims to analyze the effect of sleep duration on learning focus and memory retention among students of the Automotive Engineering Education Study Program at Universitas Pendidikan Indonesia. A quantitative descriptive approach was employed, with data collected through a structured online questionnaire consisting of 18 items across three variables: sleep duration (X), learning focus (Y1), and memory retention (Y2), using a five-point Likert scale. A total of 29 valid respondents participated in the main analysis, while 70 respondents were involved in instrument validation. Results indicate that 62% of students sleep fewer than six hours per day and 65.5% frequently stay up past 11 PM. The mean score for learning focus was 3.09 and for memory retention was 3.14 out of 5, both in the moderate category. Spearman correlation analysis revealed a positive relationship between sleep duration and learning focus (r = 0.306; p = 0.107) and memory retention (r = 0.342; p = 0.069), although neither reached conventional statistical significance, likely due to the limited sample size. Descriptive trends consistently showed higher cognitive scores among students with longer sleep durations. These findings underscore the importance of adequate sleep as a cognitive investment for academic performance and highlight the need for sleep hygiene education in university settings.